2017
DOI: 10.1089/wound.2016.0707
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Therapy for the Compromised Graft or Flap

Abstract: Tissue grafts and flaps are used to reconstruct wounds from trauma, chronic disease, tumor extirpation, burns, and infection. Despite careful surgical planning and execution, reconstructive failure can occur due to poor wound beds, radiation, random flap necrosis, vascular insufficiency, or ischemia-reperfusion (IR). Traumatic avulsions and amputated composite tissues-compromised tissue-may fail from crush injury and excessively large sizes. While never intended, these complications result in tissue loss, addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 37 publications
1
41
0
4
Order By: Relevance
“…A current review showed that HBOT is beneficial in several flap settings including dog bite, nasal defect, replantation, or war injury reconstruction [21]. The HBOT should be treated as early as possible particularly within three days after surgery [22].…”
Section: Discussionmentioning
confidence: 99%
“…A current review showed that HBOT is beneficial in several flap settings including dog bite, nasal defect, replantation, or war injury reconstruction [21]. The HBOT should be treated as early as possible particularly within three days after surgery [22].…”
Section: Discussionmentioning
confidence: 99%
“…By providing supplemental oxygen to hypoxic tissue, HBOT improves fibroblast function and collagen synthesis, leading to normal wound healing. 11 The recent European Committee for Hyperbaric Medicine (ECHM) consensus recommendations give a weak recommendation for HBOT to be used in graft or flap compromise based on a low level of evidence. 12 Interestingly, for patients at high risk of complications (e.g., history of radiation therapy to wound bed and immune compromise), they strongly recommend both pre-and postoperative HBOT, based on a low level of evidence.…”
Section: Hyperbaric Oxygenmentioning
confidence: 99%
“…Кроме того, предварительная обработка в условиях ГБО показала положительное влияние на приживаемость трансплантатов органов и лоскутов, используемых в реконструктивной хирургии ран [34,49,50].…”
Section: гипербарическая оксигенацияорганопротекторное средствоunclassified